PENANAMAN NILAI-NILAI PENDIDIKAN AGAMA ISLAM PADA PENCAK SILAT PERSAUDARAAN SETIA HATI TERATE (PSHT) DI KOMISARIAT IAIN PALANGKA RAYA - Sayid Ahmad Ramadhan; Ajahari; Yuliani Khalfiah (JIP: Jurnal Ilmu Pendidikan, 2025)
This research aims to describe efforts to instill islamic religious education values and Islamic religious education values that are instilled covering aspects of creed, worship and morals in pencak silat Persaudaraan Setia Hati Terate (PSHT) in the IAIN Palangka Raya Commissariat. This research method is qualitatively descriptive. The study subjects numbered 6 people (coaches and elders) and 5 informants (students). Data collection techniques include observations, interviews, and documentation. Data analysis through 4 stages, namely data collection, data reduction, data presentation, and conclusion/verification. The results showed that planting efforts were carried out by giving advice or advice, examples of examples, establishing silaturahim ropes, praying together when they wanted to do activities or afterwards, and inviting them to pray with students. Furthermore, the values instilled include the value of the creed, namely, obedience to God Almighty, the value of worship that is, inviting to goodness and preventing impermissibility, and moral values that are, discipline, brotherhood, mutual respect and respect for the elder and to the younger, cohesiveness, obeying and obedient to parents, coaches, elders to the applicable rules, as well as a sense of love of the homeland and culture.